The Effect of Yaker's Strategy on The Achievement of Fifth Grade Literary Students on The Achievement of Fifth Grade Literary Students In Philosophy and Psychology and The Development of Their Cognitive Curiosity - Ammar Sweid (Jurnal Psikologi, 2025)
The current research aims to study "the impact of Yaker's strategy on the achievement of fifth grade literary students in philosophy and psychology and the development of their cognitive curiosity." The researcher relied on an experimental design with partial control that includes two equivalent groups: an experimental group and a control group, commensurate with the research conditions. The researcher deliberately chose fifth grade literary students from Khalid bin Al-Walid Preparatory School in the Tikrit Education Department for the academic year (2024-2025). Through a randomized method, Division B was selected as the experimental group, with 30 students studying using the Yacker strategy. Division A was chosen as the control group, which includes 32 students studying in the traditional way. Before the start of the experiment, the researcher was keen to achieve statistical equivalence between the students of the two groups in several variables that may affect the results of the experiment, namely: the chronological age of the students calculated in months, the average of the previous school year for the third intermediate grade, the intelligence test "Raven", the academic level of fathers, the academic level of mothers, and the scores of the pre-cognitive curiosity scale. The researcher determined the educational material to be taught, which included the first and second semesters of the book "Philosophy and Psychology" for the fifth grade of literature in the Republic of Iraq. Based on the content, the researcher prepared behavioral objectives within four levels, in addition to preparing (16) the model teaching plan for each of the two groups. The researcher used two tools to measure the research variables, where the first test had an achievement test consisting of (35) items, and it verified its truthfulness, stability and discrimination, and conducted statistical analyzes of its paragraphs. In addition, the researcher developed a scale of cognitive curiosity, which in its final form consisted of (34) items, and its truthfulness, stability and distinction were also verified. After completing the experiment, the researcher applied the two research tools to the two study groups. After completing the collection of results, the research data was analyzed and appropriate statistical methods were used, and the results showed the following: 1) There is a statistically significant difference at the level of (0.05) between the average scores of the experimental group students and the average scores of the control group in the achievement test, in favor of the experimental group. 2) It was revealed that there is a statistically significant difference at the level of (0.05) between the average scores of the experimental group students and the average scores of the control group in the dimensional cognitive curiosity scale, where the results were in favor of the experimental group. 3) The results showed a statistically significant difference at the level of (0.05) in the average differences between the scores of the experimental group students in the pre- and post-tests on the cognitive curiosity scale, where the results were in favor of the post-test.